An Analysis of Spoken and Written Errors Committed by the Tenth-Grade Students of SMA Negeri 1 Kuta - Phalguna, Gede (Jurnal Pendidikan Bahasa Inggris Indonesia, 2019)
This study aimed at a) investigating the types of speech and written errors committed by the tenth-grade students of SMA Negeri 1 Kuta; b) investigating the sources of errors committed by the tenth-grade students of SMA Negeri 1 Kuta in speaking and writing. The subject of this study were the students of X science VII class. This class which consisted of 33 students; 16 males and 17 females, was chosen through purposive sampling.  The data were collected through speaking test and writing test which were analyzed descriptively. The results indicated that, first, there were 438 speech error found, consisted of anticipations (2), perseverations (2), transpositions (14), substitutions (163), deletions (189), additions (67), and haplologies (1).  Meanwhile, in writing, there were 772 errors found which consisted of grammar (623) syntax (56) dan mechanic (93). Second, the sources of errors in students’ speaking and writing were interlingual and intralingual (overgeneralization, ignorance of rule restriction, incomplete application of rules, false concept hypothesized. These findings have an important contribution to EFL teaching, specifically on teaching speaking and writing.